Terpaan Tayangan Informasi Politik di Channel Youtube Asumsi dan Partisipasi Politik Pemilih Pemula - Ardi, Ardi; Yusuf, Raidah Intizar (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2024)
This study aims in general to determine the effect of political information publication on YouTube channels on the political participation of novice voters. The type of researcher uses quantitative research, as the name implies using the survey method. In quantitative research; Survey is a type of research that uses population surveys as a means of collecting data, while the sample in this study was 385 respondents of You Tube Channel Subcribers Assumption. The results of this study indicate that media exposure has a significant effect on the political participation of young voters. The results of the study obtained a significance value of 0.000 <0.05, it can be concluded that Ha which states that there is an effect of exposure to political information impressions on the assumption you tube channel on the political participation of novice voters.